Perioperative covert stroke in patients undergoing non-cardiac surgery (NeuroVISION): a prospective cohort study. Issue 10203 (21st September 2019) - ,; Mrkobrada, Marko; Chan, Matthew T.V.; Cowan, David; Campbell, Douglas; Wang, Chew Yin; Torres, David; Malaga, German; Sanders, Robert D.; Sharma, Manas; Brown, Carl; Sigamani, Alben; et al.
Summary: Background: In non-surgical settings, covert stroke is more common than overt stroke and is associated with cognitive decline. Although overt stroke occurs in less than 1% of adults after non-cardiac surgery and is associated with substantial morbidity, we know little about perioperative covert stroke. Therefore, our primary aim was to investigate the relationship between perioperative covert stroke (ie, an acute brain infarct detected on an MRI after non-cardiac surgery in a patient with no clinical stroke symptoms) and cognitive decline 1 year after surgery. Methods: NeuroVISION was a prospective cohort study done in 12 academic centres in nine countries, in which we assessed patients aged 65 years or older who underwent inpatient, elective, non-cardiac surgery and had brain MRI after surgery. Two independent neuroradiology experts, masked to clinical data, assessed each MRI for acute brain infarction. Using multivariable regression, we explored the association between covert stroke and the primary outcome of cognitive decline, defined as a decrease of 2 points or more on the Montreal Cognitive Assessment from preoperative baseline to 1-year follow-up. Patients, health-care providers, and outcome adjudicators were masked to MRI results. Findings: Between March 24, 2014, and July 21, 2017, of 1114 participants recruited to the study, 78 (7%; 95% CI 6–9) had a perioperative covert stroke. Among the patients who completed the 1-year follow-up, cognitive decline 1 year after surgery occurred in 29 (42%) of 69 participants who had a perioperative covert stroke and in 274 (29%) of 932 participants who did not have a perioperative covert stroke (adjusted odds ratio 1·98, 95% CI 1·22–3·20, absolute risk increase 13%; p=0·0055). Covert stroke was also associated with an increased risk of perioperative delirium (hazard ratio [HR] 2·24, 95% CI 1·06–4·73, absolute risk increase 6%; p=0·030) and overt stroke or transient ischaemic attack at 1-year follow-up (HR 4·13, 1·14–14·99, absolute risk increase 3%; p=0·019). Interpretation: Perioperative covert stroke is associated with an increased risk of cognitive decline 1 year after non-cardiac surgery, and perioperative covert stroke occurred in one in 14 patients aged 65 years and older undergoing non-cardiac surgery. Research is needed to establish prevention and management strategies for perioperative covert stroke. Funding: Canadian Institutes of Health Research; The Ontario Strategy for Patient Oriented Research support unit; The Ontario Ministry of Health and Long-Term Care; Health and Medical Research Fund, Government of the Hong Kong Special Administrative Region, China; and The Neurological Foundation of New Zealand.